2016
DOI: 10.1902/jop.2016.160043
|View full text |Cite
|
Sign up to set email alerts
|

A Two‐Domain Self‐Report Measure of Periodontal Disease Has Good Accuracy for Periodontitis Screening in Dental School Outpatients

Abstract: A two-domain self-report measure combining two self-report items with age and sex has good sensitivity and specificity for periodontitis screening in a white, university-based population. The proposed self-report measure can be valuable for periodontitis screening in resource-limited settings where gold standard clinical examination may not be pragmatic. Further validation studies are required to assess whether findings from this study are context-specific.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 38 publications
(95 reference statements)
0
21
0
4
Order By: Relevance
“…Although efforts have been made to evaluate periodontal disease accurately through self‐reported measures, previous studies have shown some inconsistent results. In previous investigations, the questionnaire was used to investigate its ability to predict clinical periodontal disease severity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although efforts have been made to evaluate periodontal disease accurately through self‐reported measures, previous studies have shown some inconsistent results. In previous investigations, the questionnaire was used to investigate its ability to predict clinical periodontal disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…A recent update from the American Academy of Periodontology indicated that the classification of periodontal disease should include evaluation of the following: (i) gingival attachment level; (ii) chronic versus aggressive periodontitis; and (iii) localised versus generalised periodontitis, with a focus on the percentage of affected teeth. The second method is a subjective measurement that identifies periodontal disease through self‐reported measures. In the objective measurement, severe periodontitis is defined as having one or more site(s) with a probing pocket depth ≥ 6 mm or clinical attachment loss (CAL) ≥ 5 mm.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the validation test using the categorical periodontal classification, we suggest that this classification tends to have a wide range of periodontal status in the moderate group so that some of the subjects who answered negative for our questionnaire could have periodontal condition which is very close to mild, but classified moderate. However, our study as well as a number of previous studies has demonstrated that combinations of the two questions used in this study, namely loose teeth and professional diagnosis of gum disease, can achieve high positive predictive value for moderate to severe periodontitis (Eke et al., ; Page & Eke, ), although rather lower sensitivity rates suggest that while the self‐reported periodontitis measure used here is valid, it is likely to markedly underestimate the total number of actual cases of periodontitis in this cohort (Chatzopoulos, Tsalikis, Konstantinidis, & Kotsakis, ; Dietrich et al., ; Eke et al., ; Heaton et al., ) and compound reporting biases. However, there is little information of the accuracy of self‐reported bleeding, and thus, the phenotype of “gum bleeding” may be less robust than the presence of self‐reported periodontitis.…”
Section: Discussionmentioning
confidence: 51%